Design of a laboratory-scale reactor for the in-situ gas characterization of Fluid Catalytic Cracking (FCC) (2019)
A laboratory-scale reactor was designed and built to test optical techniques for the online and in situ monitoring of the fluid catalytic cracking (FCC) reaction progress. A one-dimensional and a three-dimensional computational fluid dynamics (CFD) model, were proposed and solved to assist in the design and to understand the hydrodynamic, mixing, heat and mass transfer phenomena taking place in the reactor. The reactor setup included Evaporation, Heating, Reaction, and Separation zones to evaporate the liquid feed, heat the catalyst particles, allow for the reaction and separate the catalyst from the gaseous stream, respectively. The reactor was a fused-quartz cylinder, 180 cm long and with an internal diameter of 1.3 cm. Five electrical furnaces that could be displaced in the vertical direction provided the heat required to maintain the gas temperature flowing in the reactor at a nominal value while provided space for passing the laser beam through the reactor to characterize the system. A mid-infrared He-Ne laser operating at 3.39 µm wavelength was used to evaluate the concentration of 1-hexene, that was selected as a model compound to represent FCC reactions. Experiments at different temperatures (373 K to 673 K) and 1-hexene concentrations (2.5 mol/m^3 to 12.5 mol/m^3), in the presence and absence of equilibrated FCC catalyst, demonstrated that the fractional transmission presents a linear response to 1-hexene concentration. Despite the fact that the optical setup did not incorporate an on-site correction for laser drift, the results are highly encouraging and suggest that inference of the advance of the FCC reaction with optical techniques in FCC systems of larger scale is possible.